Consumer Protection of Tiket.Com Application Services - Noor chalimah hapsari; Rusito Rusito (Jurnal Indonesia Sosial Teknologi, 2024)
The agreement between consumers and Tiket.com as organizers are included in the electronic agreement because it is carried out online by utilizing the sophistication of the internet Internet sophistication does not always have a positive impact, but also risks, such as abuse by irresponsible parties, for example, the case of unilateral cancellation carried out by Tiket.com due to the ban on homecoming by the government. Tiket.com canceled the trip and the consumer submitted a refund request to Tiket.com. The Tiket.com to consumers due to indications that they did not provide honesty and clarity to consumers regarding the refund. This study aims to determine and analyze consumer protection of Tiket.com application services and find legal remedies for these problems. The method used in compiling this research is a normative juridical method with descriptive research specification analysis, using secondary data obtained through literature studies with primary material. The results of this study show that Tiket.com who make unilateral cancellations related to flight tickets for indications of not providing honesty and vagueness of refunds are included in Unlawful Acts (PMH) and for the cancellation policy, Tiket.com contrary to the Consumer Protection Law and the ITE Law. To protect consumer rights, consumers can file a claim for compensation for PMH based on Article 1365 of the Civil Code.